2012
DOI: 10.1155/2012/249790
|View full text |Cite
|
Sign up to set email alerts
|

Urotensin-II: More Than a Mediator for Kidney

Abstract: Human urotensin-II (hU-II) is one of the most potent vasoconstrictors in mammals. Although both hU-II and its receptor, GPR14, are detected in several tissues, kidney is a major source of U-II in humans. Recent studies suggest that U-II may have a possible autocrine/paracrine functions in kidney and may be an important target molecule in studying renal pathophysiology. It has several effects on tubular transport and probably has active role in renal hemodynamics. Although it is an important peptide in renal ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…UII is recently shown to play a role in the immune mechanisms of tissue injury [32], [33]. In ALF, marked upregulation of UII and its receptor UTR have been demonstrated in patients [11].…”
Section: Discussionmentioning
confidence: 99%
“…UII is recently shown to play a role in the immune mechanisms of tissue injury [32], [33]. In ALF, marked upregulation of UII and its receptor UTR have been demonstrated in patients [11].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, angiotensin II increased UII and UT expression in tubular cells and UII interacts in synergy with angiotensin II. UII gene polymorphism has been also associated with some renal diseases and could be considered to streamline more relevant CKD patient populations for UT blockade (Balat and Buyukcelik, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that UT‐II plays a role in the immune mechanism of tissue damage . Changed expression of UT‐II and UTR, expression of endothelial and Kupffer cells and the correlation of these changes with specific cytokines have been shown in acute liver failure .…”
Section: Discussionmentioning
confidence: 99%